PELABELAN TOTAL TITIK AJAIB PADA COMPLETE GRAPH n K DENGAN N GENAP - Novi Irawati; Robertus Heri (Semantik, 2011)
Let G be a graph with vertex set and edge set and let andÂ .A vertex-magic total labeling of a graphÂ is a bijection mapÂ from to the integerssuch that there exists a positive integer satisfying , for every. Then k is called a magic constant and G is called vertex-magic total graph. In [5] have discussedvertex-magic labeling of complete graph for odd, now in this article, we consider a vertex-magiclabeling of complete graph for even with use an algorithm which is composed of a modifiedconstruction magic square algorithm.Keywords : vertex-magic total labeling, Complete graph , magic square